An organic cage controlling the dimension and stability of gold nanoparticles. Issue 33 (3rd April 2023) - Peters, Erich Henrik; Mayor, Marcel
Abstract : Gold nanoparticles are efficiently synthesized inside an organic cage, which controls their size, provides thermal stability, and exposes one functional group per particle. Abstract : A molecular cage encapsulating gold nanoparticles is presented. Six benzylic thioethers are pointing into its cavity, stabilizing the particles in a 1 : 1 ligand-to-particle-ratio in excellent yields. They are bench-stable for several months and can withstand unprecedented thermal stress of up to 130 °C, documenting the advantages of the cage-type stabilization over open-chain analogues.